Mutation of zebrafish dihydrolipoamide branched-chain transacylase E2 results in motor dysfunction and models maple syrup urine disease - Timo Friedrich; Aaron M. Lambert; Mark A. Masino; Gerald B. Downes (The Company of Biologists, 2012)
SUMMARY Analysis of zebrafish mutants that demonstrate abnormal locomotive behavior can elucidate the molecular requirements for neural network function and provide new models of human disease. Here, we show that zebrafish quetschkommode (que) mutant larvae exhibit a progressive locomotor defect that culminates in unusual nose-to-tail compressions and an inability to swim. Correspondingly, extracellular peripheral nerve recordings show that que mutants demonstrate abnormal locomotor output to the axial muscles used for swimming. Using positional cloning and candidate gene analysis, we reveal that a point mutation disrupts the gene encoding dihydrolipoamide branched-chain transacylase E2 (Dbt), a component of a mitochondrial enzyme complex, to generate the que phenotype. In humans, mutation of the DBT gene causes maple syrup urine disease (MSUD), a disorder of branched-chain amino acid metabolism that can result in mental retardation, severe dystonia, profound neurological damage and death. que mutants harbor abnormal amino acid levels, similar to MSUD patients and consistent with an error in branched-chain amino acid metabolism. que mutants also contain markedly reduced levels of the neurotransmitter glutamate within the brain and spinal cord, which probably contributes to their abnormal spinal cord locomotor output and aberrant motility behavior, a trait that probably represents severe dystonia in larval zebrafish. Taken together, these data illustrate how defects in branched-chain amino acid metabolism can disrupt nervous system development and/or function, and establish zebrafish que mutants as a model to better understand MSUD.